Compass visualizations for human-robotic interaction - Humphrey, Curtis M.; Adams, Julie A. (2008 3rd ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2008)
Compasses have been used for centuries to express directions and are commonplace in many user interfaces; however, there has not been work in human-robotic interaction (HRI) to ascertain how different compass visualizations affect the interaction. This paper presents a HRI evaluation comparing two representative compass visualizations: top-down and in-world world-aligned. The compass visualizations were evaluated to ascertain which one provides better metric judgment accuracy, lowers workload, provides better situational awareness, is perceived as easier to use, and is preferred. Twenty-four participants completed a within-subject repeated measures experiment. The results agreed with the existing principles relating to 2D and 3D views, or projections of a three-dimensional scene, in that a top-down (2D view) compass visualization is easier to use for metric judgment tasks and a world-aligned (3D view) compass visualization yields faster performance for general navigation tasks. The implication for HRI is that the choice in compass visualization has a definite and non-trivial impact on operator performance (world-aligned was faster), situational awareness (top-down was better), and perceived ease of use (top-down was easier).